New Generation of Orally Disintegrating Tablets for Sustained Drug Release: A Propitious Outlook - Matoug Elwerfalli, Arwa; Ghanchi, Zabir; Rashid, Fatema; G. Alany, Raid; ElShaer, Amr (Current Drug Delivery, 2015)
Orally disintegrating tablets (ODTs) or orodispersible tablets are solid dosage forms that disintegrate within 3 minutes in the mouth into a paste that can be easily swallowed. ODTs have improved over the past years, in an attempt to produce a safe and efficient substitute to the conventional oral dosage forms, particularly for dysphagia patients. Since its introduction in the market in the 1980s, ODTs expanded rapidly and achieved revenues over 3 billion in 2006 and sustaining 20% annual growth. It is therefore evident that ODTs carry good commercial value, however there is potential for improvement. Current sustained-release technologies may be exploited and incorporated into an ODT to provide greater therapeutic value by reducing the need for multiple daily dosing regimens and improving patient adherence. A number of technologies such as polymer coated nanoparticles, stimuli-responsive polymers and ion-exchange resins have emerged to produce robust, sustained release orally disintegrating tablets (SR-ODT). The purpose of this review is to highlight these various approaches and techniques and how they have been utilised in an ODT formulation to extend differentiated line, market exclusivity and patent life. The review also explores future perspective and the potential challenges that SR-ODTs will face.
Keywords: ion-exchange resin